TRANSLATION STRATEGY OF THE INTENSIFYING PREFIX RE- / RÉ- / R- FROM FRENCH INTO UZBEK LANGUAGE - Kavilova, Laura-Aquilina (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article examines the translation strategies of the French prefix re- / ré- / r- into Uzbek within the framework of pragmatic recategorization and derivational pragmatics. The research is based on contemporary linguistic theory and corpus data and is fully integrated into the theoretical model developed in the author’s doctoral dissertation on pragmatic connotations in French and Uzbek affixation. The prefix re- is analyzed not only as an iterative marker but as a pragmatically significant morpheme expressing reconstruction, intensification, emotional persistence, and subjective evaluation. Since Uzbek lacks synthetic prefixation, pragmatic equivalence is achieved through analytic constructions, lexical substitution, and contextual adaptation. Literary narrative fragments are analyzed to demonstrate translation strategies and pragmatic reinterpretation. The findings confirm that translation must preserve pragmatic function rather than morphological structure, highlighting the role of affixation as a mechanism of communicative and cognitive restructuring.